2015
DOI: 10.1111/resp.12554
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin inhibition of eosinophil differentiation attenuates allergic airway inflammation in mice

Abstract: Background and objective: The mammalian target of rapamycin (mTOR) signalling pathway regulates immune responses, and promotes cell growth and differentiation. Inhibition of mTOR with rapamycin modulates allergic asthma, while the underlying molecular mechanisms remain elusive. Here, we demonstrate that rapamycin, effectively inhibits eosinophil differentiation, contributing to its overall protective role in allergic airway inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
2
37
0
1
Order By: Relevance
“…A number of stimulatory and inhibitory factors regulate these events, including interleukin (IL)‐5 . In a mouse model of allergic asthma, rapamycin was found to attenuate allergic airway inflammation through direct inhibition of eosinophil differentiation from eosinophil progenitor cells, which was independent of IL‐5 levels . As rapamycin can inhibit the mTOR pathway (a cell cycle regulatory pathway), the findings support the importance of this pathway in allergic airway disease.…”
Section: Asthmamentioning
confidence: 76%
“…A number of stimulatory and inhibitory factors regulate these events, including interleukin (IL)‐5 . In a mouse model of allergic asthma, rapamycin was found to attenuate allergic airway inflammation through direct inhibition of eosinophil differentiation from eosinophil progenitor cells, which was independent of IL‐5 levels . As rapamycin can inhibit the mTOR pathway (a cell cycle regulatory pathway), the findings support the importance of this pathway in allergic airway disease.…”
Section: Asthmamentioning
confidence: 76%
“…Intriguingly, deletion of SGK1 in T cells makes mice resistant to experimentally induced asthma and enhances the TH1-dependant response to viral and tumor challenges. These positive effects of SGK1 inhibition could help to explain why some studies have found a positive effect of rapamycin on the immune system (Hua et al, 2015; Hurez et al, 2015). …”
Section: Mtor Signaling In the Aging Processmentioning
confidence: 91%
“…Eosinophils are a tell-tale indicator of helminth infection, where they have been shown in certain settings to play host-protective roles. Despite their importance, little is known about the role of mTOR in their biology, other than the fact that rapamycin can inhibit the IL-5-dependent proliferation and differentiation of bone marrow precursors into eosinophils (Hua et al, 2015). …”
Section: Mtor In the Innate Immune Systemmentioning
confidence: 99%